Geographical Patterns of Multidimensional Poverty and Deprivation in Uttar Pradesh - Ali, Alamtar (National Geographical Journal of India, 2022)
Based on Census data (2011) by districts this study attempts to analyze the inter-district variations in the levels of poverty as well as levels of deprivation in Uttar Pradesh. To find out the magnitude of variations among indicators of poverty and deprivation; causal relationship between level of poverty (dependent) and explanatory indicators of deprivation (independent) have been taken into account. To fulfil the objectives, Z- score, coefficient of variation, and correlation coefficient techniques have been used in this study. The study reveals that 51 per cent districts of the state recorded high level (above state average) of poverty, while 40 per cent districts witnessed high level of deprivation. Similarly, 49 per cent and 60 per cent districts registered low level (below state average) of poverty and deprivation respectively. The level of poverty is high in southeastern part of the state, and it is low in the west northern part. The level of deprivation is high in the northeastern part and low in the western and central south parts of the study area. It has been found that infant mortality rate and illiteracy rate are the major determinants of high level of multidimensional poverty among the districts of Uttar Pradesh.